(untitled) (Innovaciones Educativas, 2024)
The manuscript presents the theoretical and conceptual foundations of transdisciplinarity and eco-training and applies them to higher education through a study of their implementation in a private university in Costa Rica. Although the reflections refer to university education, they can also be applied to other educational levels or contexts. The importance of this work is highlighted by addressing the current planetary crisis and the consequent need to adapt university education to respond to it. It then provides a basic explanation of transdisciplinarity, understood as a new way of approaching reality that implies transformations for the academy. Then, the ecoformation is approached, understood as a way of life based on a balanced relationship between beings, given that everything is interconnected, and therefore committed to coexistence. For education, the ethical-philosophical principles presented can be translated into specific pedagogical and didactic concepts. Finally, it is concluded that transdisciplinarity and ecoformation are perspectives for humanity; they require a change in the traditional ways of understanding reality and, therefore, of practicing education.